Analysis of Difficulty of Mathematical Material in Primary Schools on Rounding Length and Weight Measurement Result to the Closest Denomination - Utami, Lianni Gustia; Turmudi, Turmudi; Ismail, Mochamad Tubagus (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Rounding is one of the materials available in the fourth-grade mathematics learning. Rounding is way to simplify the numbers that need to be simplified. Rounding is closely related to fairly complex numbers. Although there are no formulas in the rounding material used to calculate it, it does not make the rounding material fully understood by students. The purpose of this study in the form of written description tests given to 28 students of Asmi 033 Elementary School in Bandung. The results of the analysis show that there are difficulties faced by students in answering the rounding measurement results of the length and weight of the closest unit because the student’s ability to digest the question sentence into a mathematical sentence is still low. But there is also a possibility because the prerequisites are lacking, especially in decimal number operations